Evaluation of andrographolide from Andrographis paniculata against drug-resistant and H37Rv strains of Mycobacterium tuberculosis - Vilvest, Jelin; Milton, M C John; Yagoo, Alex; Balakrishna, Kedike (Folia microbiologica, 2025)
Tuberculosis (TB) remains a major global health concern, particularly due to the emergence of multidrug-resistant (MDR) Mycobacterium tuberculosis strains. While previous studies have suggested andrographolide as a potential antimycobacterial agent based on in silico predictions, limited empirical evidence exists on its direct efficacy against MDR-TB. This study systematically evaluates the antimycobacterial activity of andrographolide through the microbroth dilution method against M. tuberculosis H37Rv and three distinct MDR strains. The minimum inhibitory concentrations (MICs) were determined using Middlebrook 7H9 medium, with rifampicin and isoniazid as positive controls. Andrographolide completely inhibited M. tuberculosis H37Rv at an MIC of 125 µg/mL, while MICs for MDR strains varied (500 µg/mL, 125 µg/mL, and 250 µg/mL for MDR-Isolates 1, 2, and 3, respectively). Unlike previous studies that primarily relied on computational docking models, our findings provide direct experimental validation of andrographolide's strain-specific efficacy, demonstrating its potential as a promising lead compound for anti-tubercular drug development. These results underscore the need for further preclinical investigations to explore its therapeutic applications in combating drug-resistant TB.
Keywords: Andrographolide; Tuberculosis; Minimum inhibitory concentration; Multidrug-resistant; Antimycobacterial